Macro Food Policy Planning: A General Equilibrium Model for Pakistan - McCarthy, F. Desmond; Taylor, Lance (The Review of Economics and Statistics, 1980)
FOOD is macroeconomically important in poor countries, for obvious reasons. Agriculture (mainly staple food production, in most places) may make up half or more of total valueadded, and the average share of consumer expenditure going to food products is likely to be around 50% as well. Among the poor, the food budget share may be as high as three-quarters. Given all dimensions of the food sector (including production, processing, transportation and distribution activities, and consumption), the policy instruments that are supposed to influence its behavior also have noticeable macro repercussions. These have been little traced in the literature, though they can be important for all kinds of planning. In the medium to long run, for example, newly fashionable Basic Needs development strategies will require sustained growth in food intake on the part of the poorest half of the population in many countries. By Engel's Law, rapidly increasing staple food consumption imposes strong constraints on both growth and composition of aggregate demand. In the short run, food supply shortfalls and the threat of rising prices have forced more than one set of ministers to exit from the back door with rioters out front in the street. Corrective measures that they or their successors impose dramatically shift the balance of payments and government deficit positions. This paper is devoted to sketching how a simple macroeconomic model can provide guidance on how to calculate probable impacts of food policy changes in a poor country. We work specifically with Pakistan, and have tried to be as realistic as possible in designing an analytical scheme that can fit the available data, and give policy-relevant information. These requisites lead us to set up the data for accounting consistency in a Social Accounting Matrix (or SAM), discussed in the following section. Section III then outlines the structure of the analytical model built around the SAM, and section IV explains how it works. Several possible food policy interventions in Pakistan are discussed in section V, along with some implied policy conclusions. 1